Determinants of Saving in Transition Economies (1986-2006) - Codruța OSOIAN; Ioan LAZĂR; Corina GAVREA; Monica ZAHARIE (Transylvanian Review of Administrative Sciences, 2008)
In recent years it has become a common idea that a high level of saving and investment is a key element of sustained economic growth. For this reason, in this paper we analyze the determinants of saving in the transition economies in Eastern Europe with particular interest on the following: income, inflation, borrowing constraint, dependency ratio and financial liberalization and provide empirical evidence that can be used to identify the areas that need improvement for a sustained economic growth.